2016
DOI: 10.1111/odi.12420
|View full text |Cite
|
Sign up to set email alerts
|

Mouth cancer in inflammatory bowel diseases

Abstract: Mouth cancer is a major health problem. Multiple risk factors for developing mouth cancer have been studied and include history of tobacco and alcohol abuse, age over 40, exposure to ultraviolet radiation, human papilloma virus infection (HPV), nutritional deficiencies, chronic irritation, and existence or oral potentially malignant lesions such as leukoplakia and lichen planus. An important risk factor for mouth cancer is chronic immunosuppression and has been extensively reported after solid organ transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Another issue that should be taken into account is that tobacco consumption is one of the undeniable precancerous factors in the oral cavity, and although there is not a direct relationship to oral lichen planus, it is implicated in the degenerative process of oral precancerous lesions (Giagkou, Christodoulou, & Katsanos, ; López‐Jornet, Parra‐Perez, & Pons‐Fuster, ). The malignant transformation is also related to the lesion time of evolution and the patient's age.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue that should be taken into account is that tobacco consumption is one of the undeniable precancerous factors in the oral cavity, and although there is not a direct relationship to oral lichen planus, it is implicated in the degenerative process of oral precancerous lesions (Giagkou, Christodoulou, & Katsanos, ; López‐Jornet, Parra‐Perez, & Pons‐Fuster, ). The malignant transformation is also related to the lesion time of evolution and the patient's age.…”
Section: Discussionmentioning
confidence: 99%
“… 150 Additionally, IBD patients are more prone to develop mouth cancer, and the mechanisms of carcinogenesis may be linked to long-lasting inflammation, immunosuppressive treatments and to their HPV status. 151 The role of ATG16L1 loss-of-function alleles has also been reported for other cancers than HNSCC. Indeed, rs2241880 has been described as a risk factor both for developing hepatocellular carcinoma in the context of cirrhosis, 152 breast cancer, 153 and gastric cancer.…”
Section: Resultsmentioning
confidence: 89%
“…For these variables, results should be interpreted cautiously, as no firm conclusions can be drawn. Some authors 22,24 have suggested oral screening for all IBD patients, especially those who are starting immunosuppression. As the incidence of HNC in IBD in general is low and no well-defined premalignant lesions analogous to cervical intraepithelial neoplasia in cervical cancer have been established yet, we would recommend increased awareness for HNC in IBD rather than active screening, especially in elderly onset IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Various reports advocate regular oral screening. 23,24 Currently, studies on risk factor for HNC development and HNC outcome in IBD patients are lacking. We hypothesized a worse outcome for oral cavity cancer (OCC) and pharyngeal cancer (PC) in IBD patients treated with immunosuppression in comparison with the general population.…”
Section: Introductionmentioning
confidence: 99%